The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1002/cne.903480408
|View full text |Cite
|
Sign up to set email alerts
|

Octopamine‐like immunoreactivity in the brain and subesophageal ganglion of the honeybee

Abstract: The organization of putative octopaminergic pathways in the brain and subesophageal ganglion of the honeybee was investigated with a well-defined polyclonal antiserum against octopamine. Five prominent groups of just over 100 immunoreactive (IR) somata were found in the cerebral ganglion: Neurosecretory cells in the pars intercerebralis innervating the corpora cardiaca via NCC I, one cluster mediodorsal to the antennal lobe, one scattered on both sides of the midline of the protocerebrum, one between the later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
175
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 167 publications
(205 citation statements)
references
References 34 publications
22
175
0
Order By: Relevance
“…VUM mx1 belongs to a group of octopamine-immunoreactive neurons (Kreissl et al 1994). Octopamine, a biogenic amine usually associated with increased levels of arousal and behavioral facilitation in invertebrates (Libersat and Pflüger 2004;Huber 2005), had been shown to increase responsiveness of bees to olfactory stimuli (Mercer and Menzel 1982).…”
Section: Neural Bases Of Cs and Us Processingmentioning
confidence: 99%
“…VUM mx1 belongs to a group of octopamine-immunoreactive neurons (Kreissl et al 1994). Octopamine, a biogenic amine usually associated with increased levels of arousal and behavioral facilitation in invertebrates (Libersat and Pflüger 2004;Huber 2005), had been shown to increase responsiveness of bees to olfactory stimuli (Mercer and Menzel 1982).…”
Section: Neural Bases Of Cs and Us Processingmentioning
confidence: 99%
“…The distribution of octopaminergic neurons is well documented in insects including honeybees, fruit flies, blowflies, cockroaches, hawkmoths, and locusts. [105][106][107][108][109][110][111][112] The best characterized group of neuromodulatory neurons in insects constitutes a unique group of unpaired efferent median neurons, the somata of which are located at the dorsal/ventral midline of the subesophageal ganglion, thoracic, and abdominal ganglia; these neurons are known as dorsal unpaired median or ventral unpaired median neurons. [113][114][115][116] The classification of OCTlike immunoreactive neurons as clusters of cell bodies and perikarya within the cell body in the brain and the subesophageal ganglion has been reviewed elsewhere.…”
Section: Octopaminergic Neurons In the Insect Nervous Systemmentioning
confidence: 99%
“…24,108,109 A subpopulation of the subesophageal ganglion dorsal/ventral unpaired median cells innervates most parts of the brain neuropils and is involved with specific activities and complex behaviors. 105,118 The dorsal unpaired median and ventral unpaired median neurons also innervate sets of peripheral muscles, glands, and certain types of proprioceptors. 119 The peripherally released OCT from dorsal/ ventral unpaired median neurons modulates neuromuscular transmission, muscle contraction kinetics, muscle metabolism, and sensory sensitivity, and influences other properties of target organs.…”
Section: Octopaminergic Neurons In the Insect Nervous Systemmentioning
confidence: 99%
“…Kreissl et al (1991) also reported the presence of OA-IR neuronal clusters in median and lateral positions of the antennal lobes of the honeybee, where, according to physiological studies, octopamine is involved in stimulus reinforcement (Bicker and Menzel, 1989).…”
mentioning
confidence: 95%